The Influence of Explosive Power, Flexibility and Self-Confidence on the Smash Skills of Badminton Athletes at High School - Dilan Oksahmi ZT; Ahmad Adil; Andi Attsam Mappanyuki (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The smash skill in badminton is a complex technique influenced by various physical and psychological factors. However, the specific interaction between leg muscle explosiveness, wrist flexibility, and students' self-confidence levels in school sports programs still requires further analysis through a path analysis approach. This study aims to analyze the influence of leg muscle explosiveness, wrist flexibility, and self-confidence on badminton smash skills in high school students participating in sports programs. This study used a quantitative correlational method. The research sample consisted of 30 student athletes selected using a total sampling technique. The instruments used included a badminton smash skill test, a vertical jump test, wrist flexibility measurements with a protractor, and a Likert scale questionnaire for self-confidence. Data analysis was performed using descriptive statistics and path analysis through SPSS software. The results of the hypothesis test showed that leg muscle explosiveness (sig = 0.001) and self-confidence (sig = 0.000) significantly influenced smash skills. Wrist flexibility also made a significant positive contribution (sig = 0.000). Interestingly, explosive power (sig = 0.236) and flexibility (sig = 0.078) did not directly influence self-confidence, but rather indirectly through smash skill mastery. This study contributes to the development of physical education curricula and sports training programs at the high school level. These findings emphasize that to achieve optimal technique mastery, coaches and teachers must simultaneously integrate the development of physical motor skills and psychological factors.